The skull of Australopithecus afarensis - Kimbel, William H.; Rak, Yoel; Johanson, Donald C. (Human evolution series., 2004)
The book is the most in-depth account of the fossil skull anatomy and evolutionary significance of the 3.6-3.0 million year old early human species Australopithecus afarensis. Knowledge of this species is pivotal to understanding early human evolution, because 1) the sample of fossil remains of A. afarensis is among the most extensive for any early human species, and the majority of remains are of taxonomically inormative skulls and teeth; 2) the wealth of material makes A. afarensis an indispensible point of reference for the interpretation of other fossil discoveries; 3) the species occupies a time period that is the focus of current research to determine when, where, and why the human lineage first diversified into separate contemporaneous lines of descent. Upon publication of this book, this species will be among the most thoroughly documented extinct ancestors of humankind. The main focus of the book - its organizing principle - is the first complete skull of A. afarensis (specimen number A.L. 444-2) at the Hadar site, Ethiopia, the home of the remarkably complete 3.18 million year old skeleton known as "Lucy," found at Hadar by third author D. Johanson in 1974.; Lucy and other fossils from Hadar, together with those from the site of Laetoli in Tanzania, were controversially attributed to the then brand new species A. afarensis by Johanson, T. White and Y. Coppens in 1978. However, a complete skull, which would have quickly resolved much of the early debate over the species, proved elusive until second author Y. Rak's discovery of the 444 skull in 1992. The book details the comparative anatomy of the new skull (and the cast of its brain, analyzed by R. Holloway and M. Huan), as well as of other skull and dental finds recovered during the latest, ongoing field work at Hadar, and analyzes the evolutionary significance of A. afarensis in the context of other critically important discoveries of earliest humans made in recent years. In essence, it summarizes the state of knowledge about one of the central subjects of current paleoanthropological investigation